Interannual Differences for Sea Turtles Bycatch in Spanish Longliners from Western Mediterranean Sea - José C. Báez; David Macías; Salvador García-Barcelona; Raimundo Real (The Scientific World Journal)
Recent studies showed that regional abundance of loggerhead and leatherback turtles could oscillate interannually according to oceanographic and climatic conditions. The Western Mediterranean is an important fishing area for the Spanish drifting longline fleet, which mainly targets swordfish, bluefin tuna, and albacore. Due to the spatial overlapping in fishing activity and turtle distribution, there is an increasing sea turtle conservation concern. The main goal of this study is to analyse the interannual bycatch of loggerhead and leatherback turtles by the Spanish Mediterranean longline fishery and to test the relationship between the total turtle by-catch of this fishery and the North Atlantic Oscillation (NAO). During the 14 years covered in this study, the number of sea turtle bycatches was 3,940 loggerhead turtles and 8 leatherback turtles, 0.499 loggerhead turtles/1000 hooks and 0.001014 leatherback turtles/1000 hooks. In the case of the loggerhead turtle the positive phase of the NAO favours an increase of loggerhead turtles in the Western Mediterranean Sea. However, in the case of leatherback turtle the negative phase of the NAO favours the presence of leatherback turtle. This contraposition could be related to the different ecophysiological response of both species during their migration cycle.